1990
DOI: 10.1002/jat.2550100603
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronine (T3) increases cisplatin nephrotoxicity in young and adult rats

Abstract: The influence of pretreatment with triiodothyronine (T3) on cisplatin (CP)-induced nephrotoxicity was investigated in 10- and 55-day-old rats. Triiodothyronine pretreatment enhanced CP proteinuria in young and adult rats, and increased blood urea nitrogen concentration in 55-day-old rats. As T3 decreased Pt concentrations in renal tissue, the enhanced nephrotoxicity of CP by T3 must have another mechanism. Enhanced CP nephrotoxicity is discussed in connection with an increase of glutathione concentration obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…This is comparable with the investigations of Sukocheva and Carpenter [ 14 ] on mouse model of hepatotoxicity. One previous study had indicated that pretreatment with T3 enhanced CIS-induced nephrotoxicity in rats [ 37 ], the finding that was inversely demonstrated in the current work and that might be explained considering time invention. Exposure to gamma radiation was accepted to bring about dose-dependent loss of cell viability [ 38 ].…”
Section: Discussionsupporting
confidence: 54%
“…This is comparable with the investigations of Sukocheva and Carpenter [ 14 ] on mouse model of hepatotoxicity. One previous study had indicated that pretreatment with T3 enhanced CIS-induced nephrotoxicity in rats [ 37 ], the finding that was inversely demonstrated in the current work and that might be explained considering time invention. Exposure to gamma radiation was accepted to bring about dose-dependent loss of cell viability [ 38 ].…”
Section: Discussionsupporting
confidence: 54%